Cadherin-11 Deficiency Attenuates Ang-II-Induced Atrial Fibrosis and Susceptibility to Atrial Fibrillation - Cao W; Song S; Fang G; Li Y; Wang Y; Wang QS (Dove Medical Press, 2021)
Wei Cao,* Shuai Song,* Guojian Fang,* Yingze Li, Yuepeng Wang, Qun-Shan Wang Department of Cardiology, Xinhua Hospital Affiliated to Shanghai Jiaotong University School of Medicine, Shanghai, 200092, People's Republic of China*These authors contributed equally to this workCorrespondence: Qun-Shan Wang; Yuepeng Wang Email wangqunshan@xinhuamed.com.cn; wangyuepeng@xinhuamed.com.cnBackground: Atrial fibrosis serves as a disease initiating mechanism in the development of atrial fibrillation. Angiotensin II (Ang-II), a key mediator for atrial fibrosis, aberrantly activates atrial fibroblasts (AFs) into myofibroblasts, resulting in subsequent excessive synthesis and deposition of extracellular matrix (ECM). Cadherin-11 (CDH11) is essential in the development of non-cardiac fibrotic diseases. In this study, we investigated its role in the pathogenesis and underlying mechanism of atrial fibrillation.Methods: We obtained left atrial tissues from either patients with atrial fibrillation or Ang-II-induced atrial fibrosis mice. We utilized a global CDH11 knockout mouse (CDH11−/-) model to determine the effect of CDH11 on AF cell proliferation, migration, ECM synthesis/deposition. RNA-Seq of isolated AFs from CDH11−/- or normal mice was performed and differential expressed genes were analyzed. The mouse susceptibility to atrial fibrillation was examined by cardiac electrophysiology.Results: We found that cadherin-11 was significantly up-regulated in fibrotic atrial tissue from patients with atrial fibrillation and Ang-II-induced mice. Both normal and CDH11−/- mice did not develop atrial fibrosis at resting state. However, after Ang-II infusion, unlike severe atrial fibrosis occurred in normal mice, CDH11−/- mice displayed a reduced atrial fibrosis. Atrial fibroblasts with CDH11 deletion from CDH11−/- mice showed reduction in Ang-II-induced cell proliferation, migration and ECM synthesis/deposition, indicating the involvement of CDH11 in atrial fibrosis. Consistently, RNA-Seq of CDH11-null AFs uncovered significant decrease in pro-fibrotic gene expression. In addition, we identified reduction of transcripts associated with Smad2/3, ERK1/2 and JNK pathways. Further, CDH11−/- mice showed a significantly attenuated Ang-II-induced susceptibility to atrial fibrillation.Conclusion: Our results indicate that CDH11 potentiates Ang-II-induced activation of AFs. The pathogenesis of atrial fibrosis is through CDH11 mediated stimulation of Smad2/3, ERK1/2 and JNK pathways. Thus, CDH11 might serve as a novel therapeutic target for ameliorating the development of atrial fibrillation.Keywords: atrial fibrillation, atrial fibrosis, atrial fibroblast, cadherin-11, angiotensin-II